Expansion of the generating-function approach for non-rigid X2Y-type molecules by means of the Borel-type summation; Journal of Physics B: Atomic, Molecular and Optical Physics; № 33 - Starikov V. I. Vitaly Ivanovich (2000, 2000)
Title screen